A 3D/3D hetero-interpenetrated MOF with a novel (3, 9)-c net and 6-c lcy net for the fluorescence detection of carbaryl. Issue 41 (7th October 2022) - Shi, Rong; Xu, Ze-Ming; Cao, Chen; Niu, Zheng; Lang, Jian-Ping
Abstract : A 3D/3D hetero-interpenetrated MOF with a novel (3, 9)-c topology exhibits a rare yellow-green fluorescence and the fluorescence quenching effect on carbaryl. Abstract : An exceptional Zn-based MOF material with two-fold hetero-interpenetrated nets consisting of a 3D lcy network and a novel 3D (3, 9)-coordinated framework has been constructed. The Zn-based MOF exhibits a rare yellow-green fluorescence and can be used as a fluorescence sensor to detect carbaryl with a detection limit of 4.5 μM.